Effect of Holding Chamber as an Add-on Device on Aerosol Delivery and Fugitive Aerosol from Different Jet Nebulizers - Abdelrahman, Mona A.; Elberry, Ahmed A.; Hussein, Raghda R. S.; Abdelrahim, Mohamed E. (Journal of pharmaceutical innovation, 2020)
Purpose A new Circulaire II (holding chamber) was designed to be used with VixOne nebulizer to increase the inhalable doses reaching the patient. The aim of this study was to evaluate the efficacy of this holding chamber with VixOne nebulizer and determine its usability with other nebulizers. Methods The aerodynamic characteristics of emitted dose of 2 ml salbutamol solution, 5000 μg/ml, were evaluated using cooled Andersen cascade impactor at inhalation flow 15 L/min. The respirable solutions were nebulized using 3JN (VixOne, NebuTech, and En full Kit) with both holding chamber and T-piece. To evaluate the pulmonary and systemic bioavailability, 12 non-smoking health subjects (6 females), > 18 years, with an average(SD) FEV 1 > 90% of predicted, inhaled nebulized aerosol of 1 ml respirable solution (5000 μg salbutamol), diluted to 2 ml total volume using normal saline through the same nebulizer setting described above using normal tidal breathing. Subjects provided urine samples 30 min post-dosing (USAL0.5) as an index of pulmonary bioavailability and cumulatively collected their urine for 24 h (USAL24) as an index of systemic bioavailability. To determine the amount that would reach the patients (aerosol-emitted), subjects again inhaled 1 ml salbutamol-diluted respirable solution through the same nebulizer setting described above but with filters to capture salbutamol-emitted. Results Amount of salbutamol deposited in the holding chamber was significantly higher than in T-piece among all nebulizers ( p < 0.001). The fine particle fraction (FPF), < 3 μm, of VixOne with holding chamber, was significantly higher ( p < 0.001) and the mass median aerodynamic diameter (MMAD) was significantly lower ( p = 0.022) than that with T-piece. The NebuTech and Kit had lower FPF and higher MMAD with holding chamber compared to T-piece ( p < 0.05). There was no significant difference in the USAL24 and the emitted aerosol between the 3JNs with holding chamber or T-piece. Conclusions Holding chamber did not significantly increase the emitted aerosol or USAL24 responsible for the side effect but improved the FPF < 3 μm and MMAD, responsible for lung deposition, with VixOne-JN only. Holding chamber, or similar add-on device, can be used with other nebulizers other than the VixOne, not to increase the inhaled dose but as a fugitive aerosol saver.